6
$\begingroup$

This puzzle replaces all numbers with other symbols.

Your job, as the title suggests, is to find what value fits in the place of $\bigstar$. To get the basic idea, I recommend you solve Puzzle 1 first.

All symbols follow these rules:

  1. Each numerical symbol represents integers and only integers. This means fractions and irrational numbers like $\sqrt2$ are not allowed. However, negative numbers and zero are allowed.
  2. Each symbol represents a unique number. This means that for any two symbols $\alpha$ and $\beta$ in the puzzle, $\alpha\neq\beta$.
  3. The following equations are satisfied (this is the heart of the puzzle): $$ \text{I. }a\times a=a \\ \space \\ \text{II. }c<b<a \\ \space \\ \text{III. }b^c<c^b \\ \space \\ \text{IV. }d\times b+b=c \\ \space \\ \text{V. }d\times d+c+c<b\times b<d+d \\ \space \\ \text{VI. }e+b\times b\times e=d \\ \space \\ \text{VII. }a+b\times b+c+d+d+e=\bigstar $$

What is a Solution?

A solution is a value for $\bigstar$, such that, for the group of symbols in the puzzle $S_1$ there exists a one-to-one function $f:S_1\to\Bbb Z$ which, after replacing all provided symbols using these functions, satisfies all given equations.

Can you prove that there is only one possible value for $\bigstar$, and find that value?

Good luck!

Side Note: to get $\bigstar$ use $\bigstar$, and to get $\text^$ use $\text^$


Previous puzzles:

Introduction: #1 #2 #3 #4 #5 #6 #7

Inequalities: #8 #9

$\endgroup$
3
$\begingroup$

1. Let's rewrite the equations to the more readable form: $$1.\ a^2=a$$ $$2.\ c<b<a $$ $$3.\ b^c<c^b$$ $$4.\ (d+1)b=c$$ $$5.\ d^2+2c<b^2<2d$$ $$6.\ e(b^2+1)=d$$ $$7.\ a+b^2+c+2d+e=\bigstar$$ 2. Now prove that all numbers (except possibly $a$) are nonzero. Firstly, from (1) we have $a\leqslant 1$ (because either $a=0$ or $a=1$), so $b\leqslant 0$ and $c\leqslant-1$, and $c\ne0$. Next, from (4) it's obvious that $b\ne0$, Now, since $b^2>0$, then $2d$ must be also $>0$ from (5), so $d\ne0$. Finally, from (6) we get $e\ne0$.
3. If we find a solution with $a=1$, we can safely replace it with $a=0$ (and other numbers the same), and it will affect neither the equations (since $a$ is only present in conditions (1) and (2), and it's easy to see that they will still hold when we replace $a=1$ with $a=0$, since we've already proven that $b<0$ (strictly negative)) nor the uniqueness of numbers (since we've proven that $bcde\ne0$), but will change the value of $\bigstar$ (as can be easily seen from (7)). So, to prove the uniqueness of $\bigstar$, we need to prove that $a$ is necessarily $0$ (but this is not sufficient).
4. We already know that $b$ and $c$ are both negative (from (2) and the fact that $b\ne0$), and $d$ and $e$ must be positive from (5) and (6). Now let's introduce $x=-b=|b|$ and $y=-c=|c|$, so all numbers in equations will be positive (of course, except $a$).
5. Now, we get $$d^2+2c=d^2-2y=e^2(x^2+1)^2-2e(x^2+1)x-2x=(e^2x^4-2ex^3+2ex^2-(2e+2)x+e^2) < x^2,$$ or $$e^2x^4-2ex^3+(2e-1)x^2-(2e+2)x+e^2<0$$ ($e$ and $x$ being positive integers). This polynomial (let's designate it $P(x)$) does monotonically increase on $[2;+\infty)$ (here we assume that $x\geqslant 2$, but see below for $x=1$) because its derivative $P'(x)=4e^2x^3-6ex^2+(4e-2)x-(2e+2)$ is positive for $x=2$ and any $e\geqslant1$ (being $P'(2)=32e^2-18e-2$), and $P''(x)=12e^2x^2-12ex+(4e-2)$ is positive for any $x\geqslant2$ and $e\geqslant1$ (so $P'(x)$ keeps its sign, also being positive everywhere for these values of $x$). So, that means that minimum value of $P(x)$ (for $x\geqslant2$) is $P(2)=16e^2-16e+(8e-4)-(4e+4)+e^2=17e^2-12e-8$. It can be less than zero only when $e=1$ (and therefore $a=0$, due to the uniqueness requirement).
6. When $x=1$, we get $e^2-2e+(2e-1)-(2e+2)+e^2<0$, or $2e^2-2e-3<0$, which is true again only for $e=1$.
7. So, $e=1$, $a=0$, $d=x^2+1$, $x\geqslant1$ and $x^4-2x^3+x^2-4x+1<0$ (so either $x=1$ or $x=2$, i.e. $b=-1$ or $b=-2$). If $b=-1$, we get $d=2$ and $c=-3$ (Jens' solution); if $b=-2$, we get $d=5$ and $c=-12$ (Oray's solution). In both cases, $\bigstar=3$.
8. Since we have proven that no other solutions exist, the proof is complete. Q.E.D.

|improve this answer|||||
$\endgroup$
2
$\begingroup$

If

$a=0$, $b=-1$, $c=-3$, $d=2$ and $e=1$ then the equations are fulfilled and $\bigstar = 3$

|improve this answer|||||
$\endgroup$
  • $\begingroup$ is that the only solution though? $\endgroup$ – NODO55 Jan 3 at 18:43
  • $\begingroup$ This answer is exact copy of Oray... can we not just copy others answer and try to solve it ourself $\endgroup$ – Ms Designer Jan 4 at 8:51
  • $\begingroup$ @Ms Designer : Uh...this answer is not the same as Oray's answer and I posted first. $\endgroup$ – Jens Jan 4 at 10:07
2
$\begingroup$

It seems a,b,c,d,e values are not unique; here is another answer;

a=0,b=-2;c=-12,d=5;e=1 but it still makes $\bigstar$=3.

|improve this answer|||||
$\endgroup$
  • $\begingroup$ @nahmid d^2+2c<b2 $\endgroup$ – Oray Jan 3 at 19:29
  • $\begingroup$ could there be another solution? $\endgroup$ – NODO55 Jan 4 at 0:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.